Non-suicidal self-injury: The contribution of general personality functioning - Mullins-Sweatt, Stephanie N.; Lengel, Gregory J.; Grant, Demond M. (Personality and mental health, 2013)
ABSTRACT Non‐suicidal self‐injury (NSSI) is a public health problem of increasing significance. The purpose of the present study was to determine if individuals with and without a history of NSSI would differ significantly on the domains and facets of the Five Factor Model (FFM) as well as the facets from the UPPS‐P Impulsive Behaviour Scale. Self‐report measures of personality, borderline personality disorder and NSSI were administered to an undergraduate sample (n = 211). Individuals who had engaged in NSSI had significantly elevated levels of FFM facets of neuroticism (i.e. anxiousness, angry hostility, depressiveness, self‐consciousness, impulsiveness and vulnerability) and openness (i.e. aesthetics, feelings and values) and significantly lower levels of conscientiousness (i.e. order, achievement, self‐discipline and deliberation). Additionally, those with an NSSI history scored higher on UPPS‐P negative urgency, lack of premeditation and lack of perseverance. The knowledge gained from this study provides further support for personality's role in NSSI. This information may aid in the identification of risk factors for NSSI and assist in efforts examining interventions for NSSI that are targeted toward personality‐relevant strategies. Copyright © 2012 John Wiley & Sons, Ltd.